2019
DOI: 10.1002/ps.5590
|View full text |Cite
|
Sign up to set email alerts
|

Pyroxasulfone efficacy for annual ryegrass control is affected by wheat residue height, amount and orientation

Abstract: BACKGROUND Pre‐emergent herbicides play an important role in conservation agriculture, however, crop residues on the soil surface in these systems can intercept a considerable amount of herbicide during application. Cutting crops relatively high at harvest has some advantages, such as allowing faster harvest, and this also means that there is less horizontal residue on the soil surface. This field study tested the impact of standing wheat residue height and amount of horizontal residue on the interception, lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(84 reference statements)
0
3
1
Order By: Relevance
“…In the same weed, pyroxasulfone did not present differences in control due to the presence of straw; the control was excellent with 6000 kg.ha -1 of oat stubble and even when the simulated rain was 14 days after the application. These results were contradictory to those obtained with 4000 kg.ha -1 of straw, where herbicide retention resulted in less control of ryegrass (22) .…”
Section: Restrictions On the Use Of Pre-emergent Herbicidescontrasting
confidence: 90%
“…In the same weed, pyroxasulfone did not present differences in control due to the presence of straw; the control was excellent with 6000 kg.ha -1 of oat stubble and even when the simulated rain was 14 days after the application. These results were contradictory to those obtained with 4000 kg.ha -1 of straw, where herbicide retention resulted in less control of ryegrass (22) .…”
Section: Restrictions On the Use Of Pre-emergent Herbicidescontrasting
confidence: 90%
“…Loss of efficacy of the selective ACCase and ALS inhibitor herbicides has forced growers to use pre-emergent herbicides, such as trifluralin [ 88 ]. There is a broad range of pre-emergent herbicides being used for annual ryegrass control in various crops [ 89 , 90 , 91 , 92 ]. These herbicides, from distinct groups, are commonly used in rotation between years to manage annual ryegrass populations resistant to trifluralin and to minimise resistance evolution [ 78 , 89 , 92 ].…”
Section: Managementmentioning
confidence: 99%
“…Jørgensen et al (2019) [27] found that interactions between fungicide and herbicide applications were largely influenced by different farming strategies and soil conditions in winter wheat fields. Khalil et al (2020) [28] documented that stubble height and density can impact pyroxasulfone spray coverage and its efficacy. In general, rolling practices and stubble management can increase topsoil temperature and moisture, which could increase potential pathogen and weed pressure due to the relatively wet micro-climate, which in turn can interfere with the effectiveness of the pesticide.…”
Section: Interactions Among Agronomic Activitiesmentioning
confidence: 99%